HLA antigen frequencies in flax byssinosis patients. - Middleton, D (1979)
Not all workers exposed to flax dust contract byssinosis. It is not known what determines susceptibility or insusceptibility. This study is an attempt to establish whether the incidence of histocompatibility antigens is involved in susceptibility to the disease. Forty patients suffering from flax byssinosis were tissue-typed for HLA-A and -B antigens. HLA-B27 was significantly more common in the patients (22.5%) than in the controls (5.5%); P = 0.029 after correction for the number of antigens compared. HLA-A11 was present in twelve patients (30%) compared with 14% in the controls; after correction for the number of comparisons, this is not a statistically significant increase. Because HLA-B27, though significantly more common in flax byssinosis, is not necessary for its occurrence (77.5% of our patients did not have it), it is possible that the increase in the frequency of HLA-B27 is attributable to an association with other genes, perhaps those regulating the immune response or coding for antigens at other HLA loci.